Contemporary Socioeconomic and Childhood Opportunity Disparities in Congenital Heart Surgery. Issue 17 (27th September 2022) - Sengupta, Aditya; Gauvreau, Kimberlee; Bucholz, Emily M.; Newburger, Jane W.; del Nido, Pedro J.; Nathan, Meena
Abstract : Background: While singular measures of socioeconomic status have been associated with outcomes after surgery for congenital heart disease, the multifaceted pathways through which a child's environment impacts similar outcomes remain incompletely characterized. We sought to evaluate the association between childhood opportunity level and adverse outcomes after congenital heart surgery. Methods: Data from patients undergoing congenital cardiac surgery from January 2011 to January 2020 at a quaternary referral center were retrospectively reviewed. Outcomes of interest included predischarge (early) mortality or transplant, postoperative hospital length-of-stay, inpatient cost of hospitalization, postdischarge (late) mortality or transplant, and late unplanned reintervention. The primary predictor was a US census tract–based, nationally-normed composite metric of contemporary child neighborhood opportunity comprising 29 indicators across 3 domains (education, health and environment, and socioeconomic), categorized as very low, low, moderate, high, and very high. Associations between childhood opportunity level and outcomes were evaluated using logistic regression (early mortality), generalized linear (length-of-stay and cost), Cox proportional hazards (late mortality), or competing risk (late reintervention) models, adjusting for baseline patient-related factors, case complexity, and residual lesion severity. Results: Of 6133 patients meeting entry criteria, the median age was 2.0 years (interquartile range, 3.6 months–8.3 years). There were 124 (2.0%) early deaths or transplants, the median postoperative length-of-stay was 7 days (interquartile range, 5–13 days), and the median inpatient cost was 76 000 (interquartile range, 50 000–130 000). No significant association between childhood opportunity level and early mortality or transplant was observed ( P =0.21). On multivariable analysis, children with very low and low opportunity had significantly longer length-of-stay and incurred higher costs compared with those with very high opportunity (all P <0.05). Of 6009 transplant-free survivors of hospital discharge, there were 175 (2.9%) late deaths or transplants, and 1008 (16.8%) reinterventions at up to 10.5 years of follow-up. Patients with very low opportunity had a significantly greater adjusted risk of late death or transplant (hazard ratio, 1.7 [95% CI, 1.1–2.6]; P =0.030) and reintervention (subdistribution hazard ratio, 1.9 [95% CI, 1.5–2.3]; P <0.001), versus those with very high opportunity. Conclusions: Childhood opportunity level is independently associated with adverse outcomes after congenital heart surgery. Children from resource-limited settings thus constitute an especially high-risk cohort that warrants closer surveillance and tailored interventions.